Pelatihan Pencegahan Dan Mitigasi Bencana Berbasis Penguatan Manajemen Sumber Daya Manusia - Edriyani Yonlafado Simanjuntak; Formaida Tambunan; Erwin Silitonga; Maryanty Butar-Butar; Goklas Royani Sitanggang (Jurnal Pemberdayaan Masyarakat, 2026)
Indonesia is one of the countries with a high level of disaster vulnerability, including both natural and non-natural disasters, requiring systematic efforts to strengthen community capacity in disaster risk reduction. One of the key aspects in enhancing community preparedness is the strengthening of human resource management (HRM), which plays a crucial role in planning, coordination, communication, and the implementation of disaster prevention and mitigation measures. This community service program aimed to improve participants’ knowledge, skills, and preparedness through disaster prevention and mitigation training based on human resource management strengthening. The implementation methods included educational sessions, interactive training, group discussions, disaster simulations, and participant evaluations through pre-tests and post-tests. The results indicated significant improvements in participants’ understanding of disaster prevention and mitigation concepts, enhanced emergency response skills, and increased capacity to organize human resources in supporting disaster preparedness and response activities. Furthermore, participants gained better insights into the importance of leadership, coordination, communication, and effective task allocation during emergency situations. This program is expected to strengthen community capacity, enhance community resilience, and foster a sustainable disaster-aware culture through the optimization of human resource management practices